A Case of 22q11.2 Deletion Syndrome with Peters Anomaly, Congenital Glaucoma, and Heterozygous Mutation in CYP1B1. (March 2015) - Reis, Linda M.; Tyler, Rebecca C.; Zori, Roberto; Burgess, Jennifer; Mueller, Jennifer; Semina, Elena V.
Abstract We read with interest the recent publication by Tarlan and colleagues1 describing a patient with 22q11.2 deletion syndrome and ocular features of right microphthalmia and left anterior segment dysgenesis. While anterior segment dysgenesis disorders are occasionally reported with 22q11.2 deletions, 2–5 this remains a rare association. We report here an 8-year-old patient with 22q11.2 deletion syndrome and bilateral Peters anomaly with congenital glaucoma; in addition, our patient was found to have a single heterozygous mutation in CYP1B1, c.83C > T, p.(Ser28Trp).